ALKALI-CONTAINING MINERALS WITHIN MELT INCLUSIONS IN OLIVINE OF MANTLE XENOLITHS FROM BULTFONTEIN KIMBERLITE PIPE (KAAPVAAL CRATON): EVIDENCE ON HIGH CONCENTRATIONS OF ALKALIS IN KIMBERLITE MELTS - A. A. Tarasov; A. V. Golovin; I. S. Sharygin (Геодинамика и тектонофизика)
The study reports the mineral assemblage of the crystallized secondary melt inclusions in the olivine of sheared peridotites xenoliths from Bultfontein kimberlite pipe (Kaapvaal Craton, South Africa). In this type of xenoliths, the inclusions may correspond in composition to primitive kimberlite melts related to the magmatism that formed the Bultfontein pipe. Among 32 daughter phases within the inclusions, there are both ordinary rock-forming and minor minerals for kimberlites (silicates, carbonates, oxides) and "exotic" (alkali carbonates, sulfates, and chlorides) for these rocks. In the inclusions, 20 alkali-containing minerals are present, 12 of which are Na-bearing and – 4 Na-K-bearing. For instance, the inclusions contain nyerereite, K-nyerereite, shortite, gregoryite, eitelite, bradleyite, northupite, tychite, burkeite, aphthitalite, arcanite, thenardite, sylvine, and halite. On the basis of these results, the kimberlite melt of the Bultfontein pipe had Na-specification rather than Ca or K ones. The carbonates, sulfates, and chlorides significantly prevail over silicates, which content (serpentine + micas) does not exceed 16 vol. %, in the inclusions.The obtained results pose fundamental questions regarding the petrogenesis of kimberlites: (i) initial sodium concentrations in kimberlite melts and rocks, which are "traditionally" considered as very low; (ii) composition and ratio of volatile components in kimberlite magmas, namely, the initial contents of both CO2 and the components such as Cl, SO3 and H2O; (iii) primary magmatic mineral association of kimberlite rocks, which loses diverse alkali-containing minerals, but mica, due to serpentinization process.